An Empirical Analysis on the Influence of Training and Development towards Employee Performance - Sivalingam, Devagaran (2014)
Training and development have emerged into a different level of learning in recent years. Training and development have a significant role in field of Human Resources as it involves developing and maintaining the internal human resources talent pool. There are many other prior research had been done in this field of training and development. Results from those researchers showed that training and development activities comprises of few elements such as work commitment, training commitment, training needs assessment and motivation. This research attempts to contribute empirical evidence on the influence of training and development which can influence the employee performance. Questionnaires were distributed to a particular department in a multinational company. The research revealed that Training Needs Assessment, Motivation and Work Commitment are the influencing factors towards training and development which can influence the employee performance. Furthermore, Training Commitment had appeared as the most prevailing factor which the influences training and development which can influence the employee performance. The data gathered from the questionnaire had been tested statistically using SPSS and test such as Descriptive, Pearson Correlation, Regression, Validity and Reliability have been conducted. The study is concluded with discussions and recommendations for the organizations management team, human resource department and for the future researchers as well.